The Short message service or text messaging scenario in the Philippines a descriptive analysis of the word-formation processes involved in SMS or text messaging in the Philippines - League, Ivy Krystyna D.; Ver, Kathlyn R.; Santos, Maria Lorena M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
Technology is man's way of compensating what nature cannot provide. It has bridged the geographical distances between people from the different parts of the world. As technology advances, the modes of communication are becoming easier to access and more convenient to use. These technological innovations, in enhancing communication, have an effect on it as well. One of the latest innovation which has created certain modifications in the English language, one of the language's used for this form of communication. In light of these effects on the language, this particular study is concerned with how Filipinos use and modify English words in text messaging. Via an examination of theories on word-formation processes, this study gives a descriptive analysis of the modifications of existing English words in text messaging. The result of this research will then determine the underlying patterns in the way Filipinos modify English words for the purpose of text messaging.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.